Implementasi Aplikasi Holy Quran di SMP Plus Darussholah Jember - Imron Fauzi; Muhammad Yusron Irfa’ud Darojat (Edudeena : Journal of Islamic Religious Education, 2022)
Abstract: The purpose of the study is analyzing the results of the implementation of technology based learning media in learning Quran, that is through Holy Quran. This research method used descriptive qualitative with the type of case study research and data analysis techniques of the interactive model of Miles and Huberman. The result of the study shows that students can use Holy Quran application in the implementation of learning Quran, including reading Quran in accordance with the existing ‘makharijul huruf’ and ‘tajwid’, writing and understanding Quran both lexically and grammatically. Some of the advantages are (1) in the form of an application that can be run on a computer or smartphone which is very flexible, like accessable everywhere, everytime and everypeople; (2) make everything easier for user, esspesially for students in SMP Plus Darush Sholah Jember in understanding Quran through existing features, such as the theme search fitures, the tajwid and makharijul huruf fitures in reading Quran, and also the random lafadz fitures which makes it easier for students in memorizing Quran; (3) accustoming student to type Arabic letters in implementing fitures, and (4) motivating students to master Islamic Religious Education subject, considering that the majority of the Quran, through the conveniences in the Holy Quran application. Abstrak: Tujuan penelitian ini adalah menganalisis hasil implementasi dari media pembelajaran berbasis teknologi pada pembelajaran al-Quran melalui aplikasi Holy Quran. Metode penelitian ini menggunakan kualitatif deskriptif dengan jenis penelitian studi kasus serta teknik analisis data model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa peserta didik dapat menggunakan media pembelajaran berbasis teknologi berupa aplikasi Holy Quran dalam pelaksanaan pembelajaran al-Quran, meliputi membaca al-Quran sesuai dengan makharijul huruf dan tajwid yang ada, menulis dan memahami al-Quran baik secara makna leksikal maupun gramatikal. Beberapa kelebihan yang ada adalah (1) berbentuk aplikasi yang bisa di komputer atau smartphone yang sangat flexible, yakni bisa diakses dimanapun, kapanpun dan oleh siapapun; (2) memberikan kemudahan bagi pengguna, khususnya siswa SMP Plus Darussholah Jember dalam memahami al-Quran melalui fitur-fitur yang ada, seperti fitur pencarian tema, fitur tajwid dan makharijul huruf dalam membaca al-Quran serta fitur acak lafadz yang memudahkan siswa ketika menghafal ayat-ayat al-Quran; (3) membiasakan siswa dalam mengetik huruf Arab dalam mengimplementasikan fitur serta (4) memberikan motivasi kepada siswa untuk menguasai mata pelajaran Pendidikan Agama Islam, mengingat mayoritas materi yang ada adalah al-Quran, melalui kemudahan-kemudahan dalam aplikasi Holy Quran.